This is the Zero Product Property.
It says that, if:
a × b = 0 then a = 0 or b = 0 or both equal zero
So, in \(\left( b-3 \right) \left( 4+\cfrac { 2 }{ b } \right) =0\):
\(b-3=0\) and \(4+\cfrac { 2 }{ b } =0\)
Since \(b\neq 3\) then \(4+\cfrac { 2 }{ b } =0\rightarrow \left( 4+\cfrac { 2 }{ b } =0 \right) b\rightarrow 4b+2=0\rightarrow 4b=-2\rightarrow b=-\cfrac { 2 }{ 4 } \rightarrow b=-\cfrac { 1 }{ 2 }\)
_________________
"When the going gets tough, the tough gets going!"
|Welcoming tips/suggestions/advices (you name it) to help me achieve a 600|